2022
DOI: 10.1002/adma.202207280
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled Solar Energy Storage and Dark Photocatalysis in a 3D Metal–Organic Framework

Abstract: Materials enabling solar energy conversion and long‐term storage for readily available electrical and chemical energy are key for off‐grid energy distribution. Herein, the specific confinement of a rhenium coordination complex in a metal–organic framework (MOF) unlocks a unique electron accumulating property under visible‐light irradiation. About 15 C gMOF−1 of electric charges can be concentrated and stored for over four weeks without loss. Decoupled, on‐demand discharge for electrochemical reactions and H2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…) under irradiation (Figure 5h). [50] Moreover, the composite after irradiation remained stable over 4 weeks. Such long-lived reductive equivalents, specifically, radical anions, allowed the delayed discharge for on-demand hydrogen evolution.…”
Section: Decoupled Photochemical (D-pc) Catalysismentioning
confidence: 91%
See 2 more Smart Citations
“…) under irradiation (Figure 5h). [50] Moreover, the composite after irradiation remained stable over 4 weeks. Such long-lived reductive equivalents, specifically, radical anions, allowed the delayed discharge for on-demand hydrogen evolution.…”
Section: Decoupled Photochemical (D-pc) Catalysismentioning
confidence: 91%
“…For instance, Lotsch et al demonstrated that highly reductive radicals with lifetimes longer than the diurnal cycle can be formed on a cyanamide-functionalized carbon nitride polymeric network under irradiation (Figure 5g). [48] Then, the trapped electrons were released for hydrogen production in the dark, thus [40] e) Ti-MIL-125-NH 2 with the formation of reductive Ti 3 + intermediate induced by the ligand-to-metal charge transfer (LMCT), [46] f) metal oxides with oxygen vacancies as the electron trapping sites, [47] Copyright 2022, Wiley-VCH GmbH, Weinheim, g) functionalized C x N y , [48] h) MOF confined Ru-bpy hybrids, [50] i) Cu-based metal complex that can store and release two electrons, [51] and j) POMs/Ru-bpy molecular dyad integrating the properties of photosensitizers and photocatalysts. [52] Copyright 2022, Nature Publishing Group.…”
Section: Decoupled Photochemical (D-pc) Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…A kind of Zr-based MOF (bpy-UiO) was utilized as carrier to incorporate Pd NPs and to chelate metal promotes for its high stability and abundant chelation sites in ligands (bpydc). [48][49][50] Pd NPs were selected as catalytically active sites for that Pdbased catalysts usually possess certain selectivity and high activity in NS hydrogenation. Pristine Pd/bpy-UiO catalyst was prepared by loading Pd NPs uniformly onto porous bpy-UiO Moreover, the diffuse reflectance ultraviolet-visible-near infrared (UV-vis-NIR) spectrum of Pd/bpy-UiO-Cu shows obvious metal-to-ligand charge transfer band at about 740 nm (Figure 2e), which suggests strong coordination between bpydc ligand and Cu promoters.…”
Section: Preparation Of Pd/bpy-uio-cu Catalystsmentioning
confidence: 99%
“…[9][10][11] Here, porous colloids such as metal-organic frameworks (MOFs) offer unique benefits as their compositional modularity provides topologically versatile porous environments, adjustable chemical and optical properties, and high reaction surface areas. [12] In solar fuel production, various MOF-derived materials have been reported, [13][14][15] and specifically MOFs and molecular catalysts have been combined to modulate reaction environments, [16][17][18][19][20] enhance/control electron transfer, [21][22][23] or directly integrate biocatalysts. [24,25] All such composites, however, are practically constrained by framework stability in aqueous environments, moderate weight-based loading, limited light absorption mired with light scattering, and non-productive excited state quenching.…”
Section: Introductionmentioning
confidence: 99%